2019
DOI: 10.31234/osf.io/te9uz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social inequality, health behaviour determinants and health behaviour: A Systematic Review

Abstract: Objective: Health inequalities are partly due to inequalities in health behaviours. However, little is known about psychosocial mechanisms underlying health behaviour inequalities. Health behaviour determinants, e.g., those outlined in the Theoretical Domains Framework (TDF) may help understanding health behaviour inequalities. Previously two effect pathways have been theorized: behavioural determinants as mediators of the relationship between inequalities and health behaviour and inequalities as moderators of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Such resources are unequally distributed between different population groups, favoring predominantly those at the upper end of the socio-economic spectrum [17][18][19]. In this regard, it has also been found that the links between psychosocial determinants of health behavior, such as attitudes and intentions, and health behavior are more pronounced and have stronger effects on behavior among high-than among low-SEP individuals [20,21]. Thus, interventions based on these psychosocial determinants may unintentionally increase inequalities by benefiting high-SEP individuals disproportionally more.…”
Section: Introductionmentioning
confidence: 99%
“…Such resources are unequally distributed between different population groups, favoring predominantly those at the upper end of the socio-economic spectrum [17][18][19]. In this regard, it has also been found that the links between psychosocial determinants of health behavior, such as attitudes and intentions, and health behavior are more pronounced and have stronger effects on behavior among high-than among low-SEP individuals [20,21]. Thus, interventions based on these psychosocial determinants may unintentionally increase inequalities by benefiting high-SEP individuals disproportionally more.…”
Section: Introductionmentioning
confidence: 99%
“…As these resources tend to be socioeconomically patterned, whereby high-SEP individuals have relatively greater resources than those with a low SEP, interventions are likely to be more beneficial for high-SEP individuals [15,17,18]. Another explanation being discussed is that some of the psychosocial determinants of behavior operate differentially according to SEP [19,20]. Moreover, discrepancies between the perceptions of low-SEP individuals and health promoters regarding health behavior, behavior change, and support for behavior change may also result in interventions being less effective among low-SEP population groups [21].…”
Section: Introductionmentioning
confidence: 99%